Dealing With Wear: Care and Palliative Mechanisms for Compassion Fatigue - Antonio Dominguez (International Journal of Science and Society, 2020)
The Compassion Fatigue concept is common in the scientific literature of International Social Work, although surprisingly nonexistent in Spanish literature. Fatigue can be defined by compassion as a state of exhaustion and biological, psychological and relational dysfunction, the result of immediate or prolonged exposure to compassionate stress and as the final result of the progressive and cumulative process resulting from pro-longed, continuous and intense contact with clients or clients patients, the use of oneself and exposure to stress. The maintenance of the wear can lead to severe pictures typical of secondary traumatization or the onset of Burned Professional Syndrome (Burnout). In any case, if a social work professional experiences this phenomenon, their ability to empathize, connect and help their clients is severely diminished. Paradoxically, compassion fatigue is, on the one hand, necessary and inevitable if good practice is developed; on the other, dangerous and disabling if it is not compensated by other mechanisms. Compassion fatigue can not be prevented but it can and must be palliated consciously. Increasing the ability to recognize and minimize the impact of attrition is a responsibility of the professional and the organization in which he works. Finally, the work raises what to do about this phenomenon and how to take care of yourself, professionally and institutionally.